(untitled) (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2021)
This project aims to investigate the advances in automation in the clothing industry, looking for an interconnectivity between machines. Technological advances have made possible the creation of smart factories with what is known as the fourth industrial revolution; Industry 4.0 is seen as a great potential to be able to change production in the garment sector, because this industry is managed mostly by operating personnel. Therefore, this work seeks to carry out an analysis of the manufacturing process of a clothing industry, toinvestigate the new technologies that will allow to improve the processes that are carried out by labor in this industry, emphasizing the different methods that can be used for the automation of this sector.